Student Business Assistance at Al Baqalal Faculty of Islamic Studies (FPI), Universiti Kebangsaan Malaysia - Muhammad Adam; Syafruddin Chan; Faisal Faisal; Iskandarsyah Madjid; A. Sakir; Ahmad Nizam; Halimatussadiah Halimatussadiah; Darwanis Darwanis; Sofyan Idris (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This community service article delves into the entrepreneurial journey of self-employed students at the Faculty of Islamic Studies (FPI) within Universiti Kebangsaan Malaysia. These students have established a business called Al Baqalal, a convenience center catering to the culinary needs of the student community. The article highlights the community service goals aimed at enhancing the students' entrepreneurship skills and preparing them for post-graduation entrepreneurial endeavors. The report covers Al Baqalal's profile, business operations, workforce structure, and procurement schemes. It also discusses the methodology employed in the community service program, utilizing the Service Learning (SL) method. Results and discussions showcase the positive impact of mentoring on entrepreneurial students, including improvements in business foundations, marketing, financial management, and operations. The article concludes by emphasizing the significance of ongoing high-quality training, expanding the program, fostering external collaborations, conducting regular evaluations, and promoting the entrepreneurial spirit among students to further enhance the community service program's effectiveness.